Informing Parents about Newborn Screening: A European Comparison Study - Amber IJzebrink; Tessa van Dijk; Věra Franková; Gerard Loeber; Viktor Kožich; Lidewij Henneman; Marleen Jansen (MDPI AG, 2021)
Knowledge about newborn screening (NBS) is an important factor for parents to make an informed decision about participation. In Europe, countries inform parents differently about their NBS program, potentially including different knowledge aspects in their information. The aim of this study was to assess twenty-six European parental information products and to analyze their knowledge aspects through a content analysis. The analyzed aspects were compared to a list of eight knowledge aspects from scientific literature. The list includes aspects important for parents' decision-making, such as the purpose of screening. The study showed that most of the eight knowledge aspects are included in NBS information products of the majority of countries. However, there were differences between countries, for example in the amount of detail and phrasing of the information. Additional relevant knowledge aspects have also been identified and are recommended to optimize information products, such as the handling of residual bloodspot samples. This study only assessed knowledge aspects in information products meant for printing, but many countries also use other communication methods, and the impact on knowledge of the delivery of the information needs further study. Preferences of parents on alternative communication methods need to be considered and evaluated on their effectiveness.